2015
DOI: 10.1177/2051415815606847
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative use of Low Molecular Weight Heparin: Are patients doing their bit?

Abstract: Introduction: Current National Institute for Health and Care Excellence (NICE) guidelines recommend the use of Low Molecular Weight Heparin (LMWH) for one month post-operatively in abdominal and pelvic cancer surgery to reduce risk of venous thromboembolism. We audited the prescription of LMWH at discharge and the compliance of patients with LMWH post-operatively and instigated measures to improve compliance. Materials and Methods: All patients undergoing major urological surgery from November 2011 to April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Hardy et al. [29] found that 77% of patients who were prescribed postoperative LMWH after major urological surgery failed to complete the course following discharge. Over 20% of urological oncologists cite poor patient compliance as a barrier to enoxaparin use for extended VTE prophylaxis, due to factors such as difficulty and pain with injection [15,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hardy et al. [29] found that 77% of patients who were prescribed postoperative LMWH after major urological surgery failed to complete the course following discharge. Over 20% of urological oncologists cite poor patient compliance as a barrier to enoxaparin use for extended VTE prophylaxis, due to factors such as difficulty and pain with injection [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…As enoxaparin requires daily self-injection, the issue of patient adherence remains an important factor to consider when deciding between enoxaparin and apixaban, which is taken orally. Hardy et al [29] found that 77% of patients who were prescribed postoperative LMWH after major urological surgery failed to complete the course following discharge. Over 20% of urological oncologists cite poor patient compliance as a barrier to enoxaparin use for extended VTE prophylaxis, due to factors such as difficulty and pain with injection [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated the positive impact of a simple educational intervention for raising patient awareness on prophylaxis adherence following urology surgery. 18 Piloting a similar intervention across a range of sites, involving a broader range of at-risk patient groups, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 There is some evidence of similar issues of adherence among patients in the UK, 17 with some reporting adherence to LMWHs as low as 23%. 18 The guidelines also stipulate a supporting role for GPs, based on their notification of when patients are discharged and the prophylaxis prescribed. This type of communication between care settings is known to be problematic, 19 23 leaving patients vulnerable to adverse events following discharge, 24 29 and the role performed by primary care being unclear.…”
Section: Introductionmentioning
confidence: 99%